Decolourization Effects Reactive Black 5 Textile Dye Wastewater by using O3 and O3/H2O2 Process - Muhamad Azrizan Aizam Azhar (School of Environmental Engineering, University Malaysia Perlis, 2015)
To compare the performance of ozone (O3) and hydrogen peroxide (O3/H2O2) oxidation for colour and COD removal of RB5 dye waste water. To identify the effect of operational parameters of oxidation process performance, and To characterize the contaminants in dye waste water, before and after oxidation process.